2020
DOI: 10.31729/jnma.4917
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction in Out-patient Services at a Tertiary Care Center: A Descriptive Cross-sectional Study

Abstract: Introduction: Patient satisfaction is an important and commonly used valid indicator for themeasurement of service quality. Patient responses to healthcare services are one of the bestways to obtain information about patient views regarding the quality of healthcare. The mainaim of the study was to find out the patient’s satisfaction level in the tertiary care center. Methods: A descriptive cross-sectional study was conducted among 94 outpatients at a tertiary carecenter. Data were collected after obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 7 publications
(11 reference statements)
5
10
3
Order By: Relevance
“…A shortage or scarcity of such nonmedical amenities may have reduced general satisfaction. Contrast to our study, a recent study by Poudel et al in a tertiary hospital in Nepal showed a general satisfaction rate of 73% [14]. The hospital where they conducted their study is the largest public hospital in Nepal that has some super-specialized services as well; the patients' disease status and their severity may be totally different in that hospital compared to our study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…A shortage or scarcity of such nonmedical amenities may have reduced general satisfaction. Contrast to our study, a recent study by Poudel et al in a tertiary hospital in Nepal showed a general satisfaction rate of 73% [14]. The hospital where they conducted their study is the largest public hospital in Nepal that has some super-specialized services as well; the patients' disease status and their severity may be totally different in that hospital compared to our study.…”
Section: Discussioncontrasting
confidence: 99%
“…There was a wide variation in patient satisfaction across the seven dimensions in our study. A recent study conducted in the Bir Hospital, the largest public tertiary hospital in Nepal, did not show such a wide variation across the seven dimensions of patient satisfaction [14]. Such difference between that study and our study might be due to difference in service availability.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“… 33 Additionally, Poudel et al found that the percentages of satisfaction were 85.74% and 79.25%, respectively, which are slightly lower than our findings. 34 Our findings indicate that our screening staff treated the participants in an amiable and courteous manner and explained the reasons for UGC screening and related services. This can be verified by the fact that approximately 88.13% of the participants disagreed that the doctors and screening staff acted in an overly business-like and impersonal manner towards them.…”
Section: Discussionmentioning
confidence: 69%
“…et al among the armed forces in India ( 15 ), and by Poudel et al in Nepal. However, in Nepal, availability of doctors was reported as an area of concern ( 16 ).…”
Section: Discussionmentioning
confidence: 99%